Space vector modulation strategy based on volt-second balancing for three-level neutral point clamped inverter - Kanyarat Ek-Iam (2018)
© 2015 IEEE. In this paper, a methodology to apply space vector modulation (SVM) to a three-level neutral point clamped (NPC) inverter based on volt-second balancing principle is presented. The proposed scheme, switching-state selection of the three-level NPC inverter by using a nearest three vector scheme, is fully described. A mathematical analysis of the duty cycle is determined by utilizing the calculated switching time method in order to generate the duty cycle signals for both the continuous SVM (CSVM) and the discontinuous SVM (DSVM) conditions. Compared with the CSVM scheme, the DSVM scheme is the reduction in the number of commutations of switches by one third which leads to a further reduction in switching losses. Simulated results are presented to validate the proposal, which demonstrates good steady-state and dynamic performance.